LORETA functional imaging in antipsychotic-naive and olanzapine-, clozapine- and risperidone-treated patients with schizophrenia - Tislerova, Barbora; Brunovsky, Martin; Horacek, Jiri; Novak, Tomas; Kopecek, Miloslav; Mohr, Pavel; Krajca, Vladimír (Neuropsychobiology, 2008)
The aim of our study was to detect changes in the distribution of electrical brain activity in schizophrenic patients who were antipsychotic naive and those who received treatment with clozapine, olanzapine or risperidone. We included 41 subjects with schizophrenia (antipsychotic naive = 11; clozapine = 8; olanzapine = 10; risperidone = 12) and 20 healthy controls. Low-resolution brain electromagnetic tomography was computed from 19-channel electroencephalography for the frequency bands delta, theta, alpha-1, alpha-2, beta-1, beta-2 and beta-3. We compared antipsychotic-naive subjects with healthy controls and medicated patients. (1) Comparing antipsychotic-naive subjects and controls we found a general increase in the slow delta and theta frequencies over the fronto-temporo-occipital cortex, particularly in the temporolimbic structures, an increase in alpha-1 and alpha-2 in the temporal cortex and an increase in beta-1 and beta-2 in the temporo-occipital and posterior limbic structures. (2) Comparing patients who received clozapine and those who were antipsychotic naive, we found an increase in delta and theta frequencies in the anterior cingulate and medial frontal cortex, and a decrease in alpha-1 and beta-2 in the occipital structures. (3) Comparing patients taking olanzapine with those who were antipsychotic naive, there was an increase in theta frequencies in the anterior cingulum, a decrease in alpha-1, beta-2 and beta-3 in the occipital cortex and posterior limbic structures, and a decrease in beta-3 in the frontotemporal cortex and anterior cingulum. (4) In patients taking risperidone, we found no significant changes from those who were antipsychotic naive. Our results in antipsychotic-naive patients are in agreement with existing functional findings. Changes in those taking clozapine and olanzapine versus those who were antipsychotic naive suggest a compensatory mechanism in the neurobiological substrate for schizophrenia. The lack of difference in risperidone patients versus antipsychotic-naive subjects may relate to risperidone's different pharmacodynamic mechanism.
Keywords: Olanzapine; referenční hodnoty; Signal Processing, Computer-Assisted; mozek; Humans; risperidon; mapování mozku; klozapin; schizofrenie; olanzapin; dospělí; mladý dospělý; Clozapine; počítačové zpracování signálu; Female; lidé; elektroencefalografie; Schizophrenia; Brain Mapping; Adult; benzodiazepiny; antipsychotika; ženské pohlaví; Male; Brain; Benzodiazepines; Young Adult; Electroencephalography; Reference Values; Risperidone; Antipsychotic Agents; mužské pohlaví